TAX REVENUES OF BUDGETS UNITED TERRITORIAL COMMUNITIES: THEORETICAL ANALYSIS - CHYNCHYK, Anatolii; HOLUBKA, Stepan (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Using general theoretical (synthesis, induction, deduction) and special (systematization, abstraction, component analysis) methods of scientific knowledge, the article examines the features of tax management in decentralization and analyzes tax revenues of the budgets of united territorial communities in Ukraine. The article describes the features of tax management of territorial communities in the context of decentralization and considers the changes that occur as a result. In the article the authors presented his own vision of the fiscal mechanism of territorial communities in the context of decentralization in terms of fiscal planning, fiscal control, fiscal support and fiscal regulation through the prism of financial norms and standards, financial limits and gaps, financial incentives and sanctions, regulatory support.The authors claims that the visualized indicators of budget execution of territorial communities in terms of revenues, expenditures and transfers are a new tool for budget analysis at the local level. The article considers the tools of tax management of territorial communities in the conditions of decentralization in the context of four stages, which are characterized by the author.Proposals and ways to reform the tax management of territorial communities in the context of decentralization are presented, including: the need to resume the indexation of regulatory monetary valuation of land and establish the indexation coefficient at the level of the real inflation index; continuation of non-application of benefits for land plots of railway transport. The article examines four classes of united territorial communities in the conditions of decentralization according to the structure and composition of tax payments.
Keywords: tax management; financial decentralization; territorial communities; community budget; tax payments